Analisis Profil Literasi Sains Siswa Terhadap Kajian Etnosains Pada Pembuatan Ikan Salai diSMP Negeri 1 Pangkalan Kerinci - Ria Dinata; Muhammad Syafi’i; Fakhruddin Z (Journal on Education, 2024)
Scientific literacy is students' ability to understand scientific concepts and processes so that students are able to identify problems, explain scientific phenomena, and solve problems by relating human activities to everyday life. Understanding scientific concepts and processes can be integrated into the culture of a region, precisely in the Pelalawan area. One of the local wisdoms in Pelalawan, Riau is smoked fish. From the process of making fish, it has been identified that there is a scientific concept in the process of making smoked fish. The research aims to determine the profile of students' scientific literacy, especially in the context of making smoked fish. This research used a quantitative survey method with a total sample of 201 class IX students of SMP Negeri 1 Pangkalan Kerinci. Students' scientific literacy levels were measured using the students' scientific literacy instrument for making smoked fish which refers to the 2018 PISA scientific literacy competency aspect. The results of the descriptive analysis show that the scientific literacy of class IX students at SMP Negeri 1 Pangkalan Kerinci is still relatively low with an average score of 50.58%. Students' scientific literacy in the sub-context of making smoke stations is in the low category with an average score of 46.51% and in the sub-context of the process of making smoked fish is in the low category with an average score of 51.61%. Then, based on the results of the inferential analysis, it was concluded that there was no significant difference in the level of scientific literacy of male and female students.